KEBERHASILAN DAN KEGAGALAN KOMUNIKASI PUBLIK: ASPEK DAKWAH PADA GERAKAN 212 DI JAKARTA DAN GERAKAN PEMURNIAN ISLAM DI LOMBOK - Muhammad Irhamdi Irhamdi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
The practice of da’wa in a democratic society is often used as a tool to influence public policy trhough political means. This is often the case because the practice of da’wa is relatively easy to be exploited by politicians. They often transform religious messages of da’wa into political ones without loosing their attractiveness before the audience. The aim of this paper is, therefore, to aswer two inter-related questions; (1) how political messages masked with religious symbols become effective and therefore are able to influence public policy and (2) how such messages become not effective and therefore are not able to influence public policy. To answer those questions, success story in the case of 212 movement in Jakarta and a failure story in the case of religious purification of Islam in Lombok are analyzed to find elements that play important roles regarding the success and failure of a da’wa movement to influence public policy. Keywords: Public policy, Public Communication, Diffusion of Political Messages, Islamic Da’wa